Maturity differences between customer and supplier—challenges, problems, and possible solutions. Issue 3 (18th February 2013) - Kasse, Tim; Johansen, Jørn; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
SUMMARY In a globalized world, success in business today is linked with success with outsourcing. Several factors have a strong influence in this 'game'. It is our opinion that organizational maturity and process capability are very important. Low maturity in general is a problem in collaboration in a customer–supplier relationship. It is obvious that differences in maturity and process capability between customer and supplier will bring challenges and eventually problems. The insight into the difference in maturity between customer and supplier is important during the daily work—maybe even more important when a customer selects a supplier. It is here the 'landscape of problems' is formed. We have based our performance analysis on CMMI® 1.2 2 for each possible combination of difference in maturity between the customer and supplier. The problems initiated by the difference are described along with our best suggestion for possible solutions on the basis of our experiences from working with process improvement in companies worldwide. It is not possible to present the entire set of results of the performed analysis in this paper. Only the main results, argumentation, and conclusions will be presented. This paper describes the results and ends with a discussion and conclusion on the topic. Further work will go on, and the goal is to develop a simple tool to assist companies in their use of outsourcing support. This work is part of the 3‐year Danish SourceIT research project, an 18 person‐year project focusing on outsourcing and maturity, which is supported by the Danish Agency for Science Technology and Innovation under the Ministry of Science Technology and Innovation. Danske Bank, CSC Scandihealth, Nets, Roskilde University, and DELTA have been part of this project. Copyright © 2013 John Wiley & Sons, Ltd.